What differentiates the choice of certain foods? An exploratory analysis of food choice patterns among couples from the dyadic NutriAct Family Cohort in relation to social and health-associated determinants - Nadja-Raphaela Baer; Liane Schenk; Manuela M. Bergmann; Johannes Deutschbein; Sven Knüppel; Daniela Nickel; Jan C. Zoellick (Food Quality and Preference, 2025)

Unraveling the chemistry of plant flammability: Exploring the role of volatile secondary metabolites beyond terpenes - Fabián Guerrero; Lorena Espinoza; Camilo Carmona; Melisa Blackhall; Carolina Quintero; Korina Ocampo-Zuleta; Susana Paula; Javier Madrigal; Mercedes Guijarro; Yulian Carrasco; Marcela A. Bustamante-Sánchez; Alejandro Miranda; et al. (Forest Ecology and Management, 2024)

QTL mapping and transcriptome analysis identify novel QTLs and candidate genes in Brassica villosa for quantitative resistance against Sclerotinia sclerotiorum - Thomas Bergmann; Jan Menkhaus; Wanzhi Ye; Markus Schemmel; Mario Hasler; Steffen Rietz; Gunhild Leckband; Daguang Cai (Theoretical and Applied Genetics, 2023)
Key message Novel QTLs and candidate genes for Sclerotinia-resistance were identified in B. villosa , a wild Brassica species, which represents a new genetic source for improving oilseed rape resistance to SSR. Abstract Sclerotinia stem rot (SSR), caused by Sclerotinia sclerotiorum, is one of the most destructive diseases in oilseed rape growing regions. To date, there is no effective genetic resistance against S. sclerotiorum in the B. napus germplasm and knowledge of the molecular plant–fungal interaction is also limited. To identify new resistance resources, we screened a set of wild Brassica species and identified B. villosa (BRA1896) with a high level of Sclerotinia-resistance. Two segregating F 2 populations for Sclerotinia-resistance, generated by interspecific crosses between the resistant B. villosa (BRA1896) and the wild susceptible B. oleracea (BRA1909) were assessed for Sclerotinia-resistance. Genetic mapping using a 15-k Illumina Infinium SNP-array resulted in a high-density genetic map containing 1,118 SNP markers and spanning a total genetic length of 792.2 cM. QTL analysis revealed seven QTLs explaining 3.8% to 16.5% of phenotypic variance. Intriguingly, RNAseq-based transcriptome analysis identified genes and pathways specific to B. villosa, of which a cluster of five genes encoding putative receptor-like kinases (RLKs) and two pathogenesis-related (PR) proteins are co-localized within a QTL on chromosome C07. Furthermore, transcriptomic analysis revealed enhanced ethylene (ET)-activated signaling in the resistant B. villosa, which is associated with a stronger plant immune response, depressed cell death, and enhanced phytoalexin biosynthesis compared to the susceptible B. oleracea. Our data demonstrates that B. villosa represents a novel and unique genetic source for improving oilseed rape resistance against SSR.

Aggregation Pheromones of Weevils (Coleoptera: Curculionidae): Advances in the Identification and Potential Uses in Semiochemical-Based Pest Management Strategies - Pamela Taisline Bandeira; Carla Fernanda Fávaro; Wittko Francke; Jan Bergmann; Paulo Henrique Gorgatti Zarbin (Journal of Chemical Ecology, 2021)

3,7-Dimethylpentadecane: a Novel Sex Pheromone Component from Leucoptera sinuella (Lepidoptera: Lyonetiidae) - Wilson Barros-Parada; Jan Bergmann; Tomislav Curkovic; Cristian Espinosa; Eduardo Fuentes-Contreras; Jorge Guajardo; Heidy Herrera; Sebastián Morales; Abel F. O. Queiroz; Álvaro Vidal (Journal of Chemical Ecology, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Synthesis of citrophilus mealybug sex pheromone using chrysanthemol extracted from Pyrethrum ( Tanacetum cinerariifolium ) - Jan Bergmann; Jaime Tapia; Manuel Bravo; Tania Zaviezo; M. Fernanda Flores (Natural Product Research, 2019)

Plastic ingestion by juvenile polar cod (Boreogadus saida) in the Arctic Ocean - Susanne Kühn; Fokje L. Schaafsma; Bernike van Werven; Hauke Flores; Melanie Bergmann; Marion Egelkraut-Holtus; Mine B. Tekman; Jan A. van Franeker (Polar Biology, 2018)

Letter to the Editor: Official Platform for ALAEQ - Paulo H. G. Zarbin; Jan Bergmann (Journal of Chemical Ecology, 2018)

Use of Mixture Designs to Investigate Contribution of Minor Sex Pheromone Components to Trap Catch of the Carpenterworm Moth, Chilecomadia valdiviana - Stephen L. Lapointe; Wilson Barros-Parada; Eduardo Fuentes-Contreras; Heidy Herrera; Takeshi Kinsho; Yuki Miyake; Randall P. Niedz; Jan Bergmann (Journal of Chemical Ecology, 2017)

Evidence that Cerambycid Beetles Mimic Vespid Wasps in Odor as well as Appearance - Robert F. Mitchell; Tomislav Curkovic; Judith A. Mongold-Diers; Lara Neuteboom; Hans-Martin Galbrecht; Armin Tröger; Jan Bergmann; Wittko Francke; Lawrence M. Hanks (Journal of Chemical Ecology, 2017)

Identification of a Novel Moth Sex Pheromone Component from Chilecomadia valdiviana - Heidy Herrera; Wilson Barros-Parada; M. Fernanda Flores; Wittko Francke; Eduardo Fuentes-Contreras; Marcela Rodriguez; Francisca Santis; Paulo H. G. Zarbin; Jan Bergmann (Journal of Chemical Ecology, 2016)

Attraction to Host Plant Volatiles and Feeding Performance of Naupactus Xanthographus (Coleoptera: Curculionidae) is Affected by Starvation - Waleska Vera; Leonardo Parra; Andrés Quiroz; Jan Bergmann (Journal of Insect Behavior, 2016)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

HACking the centromere chromatin code: insights from human artificial chromosomes - Jan H. Bergmann; Nuno M. C. Martins; Vladimir Larionov; Hiroshi Masumoto; William C. Earnshaw (Chromosome Research, 2012)

Biological Activity of the Larval Secretion of Chilecomadia valdiviana - Luis Reyes-Garcia; M. Fernanda Flores; Waleska Vera; Jan Bergmann (Journal of Chemical Ecology, 2011)

The Absolute Configuration of the Sex Pheromone of the Citrophilous Mealybug, Pseudococcus calceolariae - C. Rikard Unelius; Ashraf M. El-Sayed; Andrew Twidle; Barry Bunn; Tania Zaviezo; M. Fernanda Flores; Vaughn Bell; Jan Bergmann (Journal of Chemical Ecology, 2011)

Comparative analysis of tumorbiology and CD133 positivity in primary and recurrent pancreatic ductal adenocarcinoma - Thilo Welsch; Shereen Keleg; Frank Bergmann; Luca Degrate; Sonja Bauer; Jan Schmidt (Clinical & Experimental Metastasis, 2009)

Identification of a Sex Pheromone Produced by Sternal Glands in Females of the Caddisfly Molanna angustata Curtis - Christer Löfstedt; Jan Bergmann; Wittko Francke; Erling Jirle; Bill S. Hansson; Vladimir D. Ivanov (Journal of Chemical Ecology, 2008)

Identification and synthesis of some fatty acid derivatives from larvae of Chilecomadia valdiviana (Lepidoptera: Cossidae) - Jan Bergmann; Katya Lopez; Gonzalo Buono-Core (Natural Product Research, 2007)

HAUSGARTEN: Multidisciplinary Investigations at a Deep-Sea, Long-Term Observatory in the Arctic Ocean - Thomas Soltwedel; Eduard Bauerfeind; Melanie Bergmann; Nataliya Budaeva; Eveline Hoste; Nina Jaeckisch; Karen von Juterzenka; Jens Matthiesson; Vadim Moekievsky; Eva-Maria Nöthig; Nadia-Valérie Quéric; Burkhard Sablotny; et al. (Oceanography, 2005)

Synthesis of the sednet work package 5 outcomes - Susanne Heise; Sabine E. Apitz; Marc Babut; Helge Bergmann; Piet den Besten; Gerald J. Ellen; Jan Joziasse; Alexandra Katsiri; Vera Maaß; Amy Oen; Adriaan Slob; Sue White (Journal of Soils and Sediments, 2004)